Complement-mediated and direct activation of human neutrophils induced by Premolis semirufa caterpillar toxins - Gabrili, Joel J. M.; Megale, Ângela A. A.; Pidde, Giselle; Woodruff, Trent M.; Tambourgi, Denise V. (Frontiers in Immunology, 2026)
IntroductionPararamosis is an occupational inflammatory disease caused by contact with hairs of the caterpillar Premolis semirufa, endemic to the Brazilian Amazon and primarily affecting rubber tree workers. Exposure to pararama hairs induces acute pruritic dermatitis and, in some cases, chronic joint inflammation resembling rheumatoid arthritis and osteoarthritis. Previous studies demonstrated that pararama hair extract activates the complement system and induces a robust inflammatory response in mouse models, characterized by cytokine production and immune cell recruitment. Given the critical role of neutrophils in inflammation and their activation by complement components, this study investigated the effects of pararama hair extract on human peripheral blood neutrophils.MethodsNeutrophils isolated from healthy donors were directly stimulated with the extract or incubated with plasma derived from whole blood treated with the extract, in the presence or absence of compstatin, a C3 inhibitor that blocks complement activation, and PMX205, a selective C5aR1 antagonist applied directly to neutrophils. We assessed neutrophil activation by measuring cytokine and chemokine secretion, myeloperoxidase and elastase release, and neutrophil extracellular trap (NET) formation.ResultsOur results reveal that pararama hair extract directly activates neutrophils, enhancing pro-inflammatory mediator release and degranulation. Moreover, plasma from extract-treated human whole blood samples further potentiated neutrophil activation, which was significantly reduced by compstatin, through inhibition of C3, and by selective blockade of the C5a receptor (C5aR1).DiscussionThese findings highlight the integrated role of complement in neutrophil activation, as compstatin broadly inhibited complement-dependent effects, while PMX205 demonstrated the specific contribution of the C5a–C5aR1 axis. Targeting complement thus emerges as a promising strategy to mitigate inflammation and tissue damage in affected individuals.